Schizosaccharomyces pombe RanGAP Homolog, SpRna1, Is Required for Centromeric Silencing and Chromosome Segregation - Kusano, Ayumi (The American Society for Cell Biology, 2004)
We isolated 11 independent temperature-sensitive (ts) mutants of Schizosaccharomyces pombe RanGAP, SpRna1 that have several amino acid changes in the conserved domains of RanGAP. Resulting Sprna1(ts) showed a strong defect in mitotic chromosome segregation, but did not in nucleocytoplasmic transport and microtubule formation. In addition to Sprna1(+) and Spksp1(+), the clr4(+) (histone H3-K9 methyltransferase), the S. pombe gene, SPAC25A8.01c, designated snf2SR(+) (a member of the chromatin remodeling factors, Snf2 family with DNA-dependent ATPase activity), but not the spi1(+) (S. pombe Ran homolog), rescued a lethality of Sprna1(ts). Both Clr4 and Snf2 were reported to be involved in heterochromatin formation essential for building the centromeres. Consistently, Sprna1(ts) was defective in gene-silencing at the centromeres. But a silencing at the telomere, another heterochromatic region, was normal in all of Sprna1(ts) strains, indicating SpRna1 in general did not function for a heterochromatin formation. snf2SR(+) rescued a centromeric silencing defect and Δclr4(+) was synthetic lethal with Sprna1(ts). Taken together, SpRna1 was suggested to function for constructing the centromeres, by cooperating with Clr4 and Snf2SR. Loss of SpRna1 activity, therefore, caused chromosome missegregation.